Built-in Motion Sensor Bedside Table Inspired by Tangram - Cai Tian, Ng; Selimin, Mohamad Ali (Research in Management of Technology and Business, 2021)
With the revolutions of technology, integration of traditional furniture and high-tech upgraded into the new generation of furniture, which is smart furniture able to make our daily activities much easier. Waking up in the middle of the night for a bathroom without sufficient lighting is a distressing thing and also might lead to an avoidable accident due to the dark environment (poor visibility). Therefore, the purpose of the study is to design and develop a built-in motion sensor bedside table inspired by Tangram. The questionnaire was distributed via Google Form to the respondents aged 20 years old and above in Batu Pahat, Johor in order to obtain the design criteria of designing the bedside table. Subsequently, the design process of the bedside table started with visual research, thumbnail and ideation sketches, idea development, final design selection, mock-up, and ends with prototype fabrication. The prototype of the built-in motion sensor bedside table was made of plywood and finished with varnish. The findings showed that the built-in motion sensor bedside table was designed with flexible storage boxes that can be arranged or reposition according to the users’ preferences. This study was successfully developed a new design of bedside table with built-in motion sensor light that meets the market demand as a remedy to the aforementioned problem.